2009
DOI: 10.1016/j.ijhcs.2009.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Perceived interactivity leading to e-loyalty: Development of a model for cognitive–affective user responses

Abstract: A B S T R A C T 1Novel applications of website interactivity are important to attract and retain online users. In this empirical study five designs for interactivity are examined using different web-poll interfaces. The goal of the investigation is to examine perceived interactivity in a model which includes most commonly tested cognitive elements such as efficiency and effectiveness, but augments this model with the inclusion of a cognitive-affective element for trust, and an affective element of enjoyment. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
225
5
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(247 citation statements)
references
References 62 publications
9
225
5
8
Order By: Relevance
“…engagement). Cyr, Head and Ivanov (2009) In contrast, Yi, Jiang and Benbasat (2011) found that limiting the opportunity to interact with products was more effective than video presentation or unconstrained interaction, concluding that limiting interaction may evoke curiosity and hence may be more persuasive in marketing.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…engagement). Cyr, Head and Ivanov (2009) In contrast, Yi, Jiang and Benbasat (2011) found that limiting the opportunity to interact with products was more effective than video presentation or unconstrained interaction, concluding that limiting interaction may evoke curiosity and hence may be more persuasive in marketing.…”
Section: Related Workmentioning
confidence: 99%
“…Many definitions of interactivity have been produced, varying from Hoffman and Novak's (1996) categories of machine (UI controls) and person interaction (i.e. Computer Mediated Communication, or CMC), to Kristof and Satran's (2002) sevenlevel 'control over' grading of features used by Teo et al (2003); and Lee's (2005) framework of control, connectedness, and responsiveness, used in Cyr et al's studies (Cyr, Head & Ivanov 2009;Cyr, Head, Larios & Pan, 2009). Researchers in multi-media learning have proposed multi-faceted models of interactivity (Domagk, Schwartz & Plass 2010;Moreno & Mayer (1999) involving features for personalisation and user adaptation, interactive simulations or microworlds, as well as CMC between learners and tutors.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Lee et al [111], in a sample of 289 online customers, identified the key design factors for customer loyalty, and they found a strong impact of trust on customer loyalty (path coefficient = 0.781, p<0.01). Also, Gefen [67] investigated the influence of service quality on trust and loyalty, and the findings again showed a similar positive direct relationship between trust and loyalty. However, some researchers have found slight or even no association between trust and loyalty.…”
Section: After-purchase Factorsmentioning
confidence: 78%